Performance Standards and Employee Effort: Evidence from Teacher Absences - Seth Gershenson (Institute for the Study of Labor (IZA), 2015)
The 2001 No Child Left Behind Act (NCLB) increased accountability pressure in U.S. public schools by threatening to impose sanctions on Title-1 schools that failed to make Adequate Yearly Progress (AYP) in consecutive years. Difference-in-difference estimates of the effect of failing AYP in the first year of NCLB on teacher effort in the subsequent year suggest that on average, teacher absences in North Carolina fell by about 10% and the probability of being absent 15 or more times fell by about 20%. Reductions in teacher absences were driven by within-teacher increases in effort.
Keywords: J45; J48; J22; I2; 330; performance standards; employee effort; teacher absences; accountability; NCLB